ANALISIS FAKTOR SOSIAL DAN BUDAYA KONSUMEN DALAM MEMPENGARUHI PERILAKU PEMBELIAN PRODUK ALFAMART SUMBAWA BESAR - Muhrayanti, Sulis; Sutama, I Nyoman (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to analyze the effect of consumer social and cultural factors on products purchasing decision at alfamart Sumbawa Besar. The type of this study was associative which aims to examine the relationship or effect between two or more variables. The type of data used in this study was quantitative data in the form of scoring results of respondents' answers regarding the object under study. The data was collected directly by researchers from the original source, namely Alfamart consumers on the Karang Dima Bypass Road, Sumbawa Besar, which was the research location. The number of samples used as respondents in this study was 100 people who were selected using accidental sampling techniques. The data that has been collected was processed using the SPSS application to be studied using simple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient test (R2). The results of this study showed that the social factors did not had effect on product purchasing decisions at Alfamart Sumbawa Besar, while the cultural factors had positive and significant effect on product purchasing decisions at Alfamart Sumbawa Besar. Then simultaneously that the consumer social and cultural factors had a significant effect on product purchasing decisions at Alfamart Sumbawa Besar. The effect of consumer social and cultural factors on product purchasing decisions at Alfamart Sumbawa Besar was 36.1%, while the remaining of 63.9% was affected by other variables outside this study, such as marketing mix factors: product, price, place, and promotion.